2019
DOI: 10.1186/s13071-019-3521-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of oral fluralaner for the treatment of canine generalized demodicosis: a molecular-level confirmation

Abstract: Background Canine generalized demodicosis is a common parasitic disease caused by the proliferation of Demodex mites. The introduction of isoxazoline class treatments in veterinary dermatology has resulted in apparently effective treatment of generalized demodicosis. The objective of this study was to evaluate the effectiveness of fluralaner for the treatment of canine generalized demodicosis using real-time PCR for the detection and quantification of Demod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
9
0
4
Order By: Relevance
“…Three consecutive treatments at 4-weekly or monthly intervals were used in separate studies of sarolaner [11] and afoxolaner [12], and in an uncontrolled study with lotilaner [13]. Two studies, one of which was uncontrolled, investigated single-treatment uralaner e cacy using the chewable formulation [10,23], and one controlled study involved the spot-on formulation [17]. The multiple treatments with afoxolaner, sarolaner, and lotilaner, and the single treatment controlled study with either uralaner formulation, all reduced mean demodectic mite counts by >99% within the month following the day 0 treatment, and by 100% at days 81 or 84.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three consecutive treatments at 4-weekly or monthly intervals were used in separate studies of sarolaner [11] and afoxolaner [12], and in an uncontrolled study with lotilaner [13]. Two studies, one of which was uncontrolled, investigated single-treatment uralaner e cacy using the chewable formulation [10,23], and one controlled study involved the spot-on formulation [17]. The multiple treatments with afoxolaner, sarolaner, and lotilaner, and the single treatment controlled study with either uralaner formulation, all reduced mean demodectic mite counts by >99% within the month following the day 0 treatment, and by 100% at days 81 or 84.…”
Section: Discussionmentioning
confidence: 99%
“…Across those studies, the reported e cacies of imidacloprid-moxidectin within the month after the rst treatment ranged from 9.8 to 89.8%, and on day 84, following multiple treatments, from 0 to 100%. In the uncontrolled oral uralaner study, PCR analysis of hair collected from treated dogs found that Demodex DNA levels progressively declined throughout the study, and on day 112 were reduced 1000-fold from pre-treatment levels [23]. Thus, the accumulating data in which the isoxazolines have shown potent e cacy and superiority over imidacloprid-moxidectin indicate that they would be the treatment of choice for generalized demodicosis, although further controlled studies would be helpful to con rm that the miticidal e cacy of afoxolaner and lotilaner is maintained under eld conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Three consecutive treatments at 4-weekly or monthly intervals were used in separate studies of sarolaner [11] and afoxolaner [12], and in an uncontrolled study with lotilaner [13]. Two studies, one of which was uncontrolled, investigated single-treatment fluralaner efficacy using the chewable formulation [10,23], and one controlled study involved the spot-on formulation [17]. The multiple treatments with afoxolaner, sarolaner and lotilaner, and the single treatment controlled study with either fluralaner formulation, all reduced mean demodectic mite counts by > 99% within the month following the Day 0 treatment, and by 100% at Days 81 or 84.…”
Section: Discussionmentioning
confidence: 99%
“…Three consecutive treatments at 4-weekly or monthly intervals were used in separate studies of sarolaner [11] and afoxolaner [12], and in an uncontrolled study with lotilaner [13]. Two studies, one uncontrolled, investigated single-treatment fluralaner efficacy using the chewable formulation [10,23], and one controlled study involved the spot-on formulation [17]. The multiple treatments with afoxolaner, sarolaner, and lotilaner, and the single treatment controlled study with either fluralaner formulation, all reduced mean demodectic mite counts by >99% within the month following the day 0 treatment, and by 100% at days 81 or 84.…”
Section: Discussionmentioning
confidence: 99%
“…Across those studies, the reported efficacies of imidacloprid-moxidectin within the month after the first treatment ranged from 9.8 to 89.8%, and on day 84, following multiple treatments, from 0 to 100%. In the uncontrolled oral fluralaner study, PCR analysis of hair collected from treated dogs found that Demodex DNA levels progressively declined throughout the study, and on day 112 were reduced 1000-fold from pre-treatment levels [23]. Thus, the accumulating data in which the isoxazolines have shown potent efficacy and superiority over imidacloprid-moxidectin indicate that they would be the treatment of choice for generalized demodicosis, although further controlled studies would be helpful to confirm that the miticidal efficacy of afoxolaner and lotilaner is maintained under field conditions.…”
Section: Discussionmentioning
confidence: 99%